Downregulation of TAP1 in Tumor-Free Tongue Contralateral to Squamous Cell Carcinoma of the Oral Tongue, an Indicator of Better Survival - Attaran, Nima; Gu, Xiaolian; Coates, Philip J; Fåhraeus, Robin; Boldrup, Linda; Wilms, Torben; Wang, Lixiao; Sgaramella, Nicola; Zborayova, Katarina; Nylander, Karin (International journal of molecular sciences, 2020)
Oral cancers are surrounded by epithelium that histologically might seem normal, but genetically has aberrations. In patients with squamous cell carcinoma of the oral tongue (SCCOT), it is therefore important to study not only the tumor but also the clinically tumor-free contralateral tongue tissue that remains in the patient after treatment to map changes of prognostic and/or diagnostic value. The transporter associated with antigen processing (TAP) dimer is a key factor in the process of activating cytotoxic T cells. By downregulating the expression of TAP, tumor cells can escape cytotoxic T cell recognition. Biopsies from tumor and clinically tumor-free contralateral tongue tissue in 21 patients with SCCOT were analyzed together with tongue biopsies from 14 healthy individuals, which served as the control group. Dividing patients into TAP1-high and TAP1-low groups according to the median TAP1 level in tumor-free samples showed that patients with lower TAP1 mRNA levels in tumor-free samples had better overall (p = 0.003) and disease-free survival (p = 0.002). The results showing that TAP1 levels in tumor-free tongue tissue contralateral to the SCCOT correlate with survival is an important contribution to early diagnosis and follow up of SCCOT.
Keywords: senioři; analýza přežití; Early Detection of Cancer; TAP1; spinocelulární karcinom; MHC I; senioři nad 80 let; Male; Survival Analysis; Prognosis; regulace genové exprese u nádorů; down regulace; Middle Aged; mužské pohlaví; Biopsy; studie případů a kontrol; Adult; field cancerization; Tongue Neoplasms; časná detekce nádoru; nádory jazyka; Biomarkers, Tumor; Down-Regulation; Aged, 80 and over; ženské pohlaví; nádorové biomarkery; prognóza; Humans; Gene Expression Regulation, Neoplastic; SCCOT; lidé středního věku; ATP Binding Cassette Transporter, Subfamily B, Member 2; biopsie; Tongue; dospělí; Carcinoma, Squamous Cell; Female; Aged; peptidový transportér TAP1; lidé; Case-Control Studies; jazyk